Analisis Faktor Eksternal dan Faktor Internal yang Mempengaruhi Marketing Reach pada Perkembangan UMKM: Studi Kasus pada UMKM di Kabupaten Serdang Bedagai - Wahyu Fitria Anggraini; Rahmayati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Micro, Small and Medium Enterprises have the ability to create jobs at minimum cost. Small and medium-sized companies are pioneers in the world of innovation and have high flexibility that allows businesses to meet customer needs. The type of research used is quantitative. The population in this research is MSME owners in Serdang Begadai district, based on data from the Serdang Begadai District Government until 2023 who come from the fields of agriculture, trade, services and small industry. Until now, not many MSMEs have implemented go digital (Serdang Begadai Regency Government, 2024), the sampling method used in this research is Probability Sampling (Random Sample), the type used is Cluster Sampling. Before testing the hypothesis, a prerequisite test for proving the hypothesis is carried out. In this study, the model used by the researcher is multiple linear regression. Based on the research results, it can be concluded that in general the role and existence of external and internal factors are recognized as factors and figures of interest through government, social and economic policies as well as the role of related institutions in running a business because business actors cannot run alone to carry out and develop business. External and internal factors that are indicated to have a positive influence are the capital aspect, that basically most business actors when running their business tend to prefer to use their own capital rather than taking out loans because they feel more at ease using their own capital